Effect of Carica papaya Leaf Juice on Bone Marrow Aspirate of Busulfan-induced Chronic Bone Marrow Aplasia in Mice - Sofia Yasmeen Abbasi, Muniza Qayyum, Gul Pash Saghir, Sadia Chiragh, Fauzia Kanwal, Nazia Rashid (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Aplastic anemia is a disorder characterized by peripheral pancytopenia and hypoplastic bone marrow. Papaya, botanical name Carica Papaya, is a tropical fruit with a wide range of benefits. In past couple of years, researches have been carried out on beneficial outcomes of papaya leaf juice on blood and bone marrow, particularly platelet count. Aim: Taking into consideration the beneficial effects of papaya leaves on bone marrow, current research was done to probe the effects of C.papaya leaf juice on bone marrow differential cell count and cellularity in myelosuppressed mice where busulfan was used to induce myelosuppression. Study Design: Experimental. Place and Duration of Study: our study was performed in Post Graduate Medical Institute, Lahore in one year time. Materials & Methods : It was an animal experimental study of 23 days in which 36 adult healthy swiss albino mice weighing 30-35 g of either sex were segregated into three groups with 12 mice in each group. Busulfan at a dose of 14mg/kg was given orally to the busulfan group to induce myelosuppression and to the C.papaya +busulfan group on 8 occassions (0, 3,8,11,15,18,21&23) for a duration of 23 days. To observe the myeloprotective effect of Carica papaya leaf juice 10ml/kg of juice was given to the C.papaya + busulfan group daily for 23 days. After the final dose of busulfan and Carica papaya leaf juice on day 23, the samples for bone marrow aspirate were collected on same day. Results: The current study has revealed that C.papaya leaf juice not only prevented a decrease in all parameters of bone marrow aspirate but also maintained their normal values close to normal. The megakaryopoiesis was however found to be significantly higher than the normal. Keeping in view these beneficial effects carica papaya leaf juice can be used in chemotherapy induced thrombocytopenia and other related clinical conditions. Conclusion: it can be concluded from this study that C.papaya can be used in all such conditions that lead to fall in chemotherapy induced thrombocytopenia because of its property to increase megakaryopoiesis. Keywords: C.papaya, Busulfan, Megakaryopoiesis, Bone marrow failure.